The conflict in team management impact to team performance - Nur Hazwani , Jamal (2014)
Conflict reflects on team performance. Any unresolved conflicts in work team will affect the performance of team. So, the purpose of this research is to identify the conflicts in team management, and to identify the relationship between the conflicts in team management to the team performance. The main things need to be covered are the conflict faced in team management and the relationship between the conflict in team management toward the team performance. Those two main things will be determined and analyzed in this research. The relationship of the conflict in team management toward the team performance are just to identify either the conflict in team management have an impact toward team performance or not. So, for this study, that have two variables which is type of conflict is the independent variable and atmosphere in team performance as dependent variable. Survey techniques are used for the data collection. The sample size use in this study is 24 of respondents out of 30 of companies from the population. The questionnaire was distributed to the construction company as the respondents are those who work as a team in construction companies. The result will be obtained by using SPSS Software and the result shows the both of the objectives were achieved. The first objective will comes out by three types of conflict faces in the team structure which is task conflict, relationship conflict and process conflict. The second objective achieve after we comes out by the type of the conflict with the atmosphere among the team structure in construction companies. For the impact between the conflicts and the team performance there is have a significant impact between two variables but only faced in the process conflict. The other two of the conflict which is task conflict and relationship conflict doesn’t have leaves a significant impact toward the atmosphere in the team performance